Two new polyketides from Hawaiian endophytic fungus Pestalotiopsis sp. FT172 - Li, Chunshun (2018)
Two new polyketides, pestalotiotones A (1) and B (2) were isolated from the cultured broth of Pestalotiopsis sp. FT172. The structures of compounds 1 and 2 were determined by analysis of HRMS and NMR spectroscopic data. The absolute configurations of compound 1 were assigned by Mosher reaction, J-based configuration analysis, and DP4 NMR calculations. Both compounds were tested against cancer cell lines, pathogenic fungi and bacteria.